Developing a citizen technician based approach to suspended sediment monitoring in the Tsitsa River catchment, Eastern Cape, South Africa - Bannatyne, Laura Joan (Rhodes University, Faculty of Science, Department of Geography, 2018)
Suspended sediment (SS) in channels is spatiotemporally heterogeneous and, over the long term, is known to be moved predominantly by flood flows with return periods of ~1 - 1.5 years. Flood flows in the Tsitsa catchment (Eastern Cape Province, South Africa) are unpredictable, and display a wide range of discharges. Direct, flood-focused SS sampling at sub-catchment scale was required to provide a SS baseline against which to monitor the impact on SS of catchment rehabilitation interventions, to determine the relative contributions of sub-catchments to SS loads and yields at the site of the proposed Ntabelanga Dam wall, and to verify modelled SS baselines, loads and yields. Approaches to SS sampling relying on researcher presence and/or installed equipment to adequately monitor SS through flood flows were precluded by cost, and the physical and socioeconomic conditions in the project area. A citizen technician (CT)-based flood-focused approach to direct SS sampling was developed and implemented. It was assessed in terms of its efficiency and effectiveness, the proficiency of the laboratory analysis methods, and the accuracy of the resulting SS data. A basic laboratory protocol for SSC analysis was developed, but is not the focus of this thesis. Using basic sampling equipment and smartphone-based reporting protocols, local residents at eleven points on the Tsitsa River and its major tributaries were employed as CTs. They were paid to take water samples during daylight hours at sub-daily timestep, with the emphasis on sampling through flood flows. The method was innovative in that it opted for manual sampling against a global trend towards instrumentation. Whilst the management of CTs formed a significant project component, the CTs benefitted directly through remuneration and work experience opportunities. The sampling method was evaluated at four sites from December 2015 - May 2016. The CTs were found to have efficiently and effectively sampled SS through a range of water levels, particularly in the main Tsitsa channel. An acceptable level of proficiency and accuracy was achieved, and many flood events were successfully defined by multiple data points. The method was chiefly limited by the inability of CTs to sample overnight rises and peaks occurring as a result of afternoon thunderstorms, particularly in small tributaries. The laboratory process was responsible for some losses in proficiency and accuracy. Improved laboratory quality control was therefore recommended. The CT-based approach can be adapted to other spatial and temporal scales in other areas, and to other environmental monitoring applications.
Keywords: Sediments (Geology) -- Management; Sediments (Geology) -- South Africa -- Eastern Cape; Watersheds -- South Africa -- Eastern Cape; Suspended sediments -- South Africa -- Eastern Cape; Suspended sediments -- Monitoring -- Citizen participation; Tsitsa River